Peranan senam irama terhadap kebugaran jasmani untuk siswa sekolah dasar - Pasaribu, Ahmad Muchlisin Natas; Mashuri, Hendra (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
Physical fitness for elementary school children is a major aspect in supporting children's growth and development. The purpose of this study was to determine the effect of rhythmic gymnastics on physical fitness. This research is a pre-experimental research with a single group pretest-posttest design. The sampling technique used a saturated sampling technique or total sampling with 30 students. Then the data collection techniques in this study were conducted using the Indonesian Physical Fitness Test (TKJI) for ages 6-9 years. The results of the study found that the relative contribution of the use of rhythmic gymnastics increased with the results of pretest / posttest = 10.87 / 19.77 x 100% = 54.98%. Thus the contribution of more than 50% means rhythmic gymnastics in this study can be said to be effective for improving physical fitness of children in elementary schools and for 45.02% can be obtained from other treatments.